2017
DOI: 10.1021/acs.jmedchem.6b01718
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design, Synthesis, and Biological Evaluation of Heterocyclic Quinolones Targeting the Respiratory Chain of Mycobacterium tuberculosis

Abstract: A high-throughput screen (HTS) was undertaken against the respiratory chain dehydrogenase component, NADH:menaquinone oxidoreductase (Ndh) of Mycobacterium tuberculosis (Mtb). The 11000 compounds were selected for the HTS based on the known phenothiazine Ndh inhibitors, trifluoperazine and thioridazine. Combined HTS (11000 compounds) and in-house screening of a limited number of quinolones (50 compounds) identified ∼100 hits and four distinct chemotypes, the most promising of which contained the quinolone core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 60 publications
0
36
0
Order By: Relevance
“…Because redox homeostasis is important for the survival of cells in a slowing-replicating state (27,28), Ndh inhibitors might also be good candidates to target persister or dormant Mtb bacteria. In that context, new Ndh inhibitors have been synthesized and shown to have antimycobacterial activity under aerobic and hypoxic conditions against both drug-susceptible and drug-resistant Mtb strains (29). Furthermore, redox homeostasis is also an important factor in drug activity and resistance, since many drugs against Mtb are prodrugs activated via a reductive process.…”
Section: Discussionmentioning
confidence: 99%
“…Because redox homeostasis is important for the survival of cells in a slowing-replicating state (27,28), Ndh inhibitors might also be good candidates to target persister or dormant Mtb bacteria. In that context, new Ndh inhibitors have been synthesized and shown to have antimycobacterial activity under aerobic and hypoxic conditions against both drug-susceptible and drug-resistant Mtb strains (29). Furthermore, redox homeostasis is also an important factor in drug activity and resistance, since many drugs against Mtb are prodrugs activated via a reductive process.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] In particular,t he synthesis of the fluoroquinolone family of compounds has made ag reat contribution to anti-infective agents, such as norfloxacin,c iprofloxacin, levofloxacin, and moxifloxacin. [4,5] The antimicrobialm echanism revealed that this type of drug could target DNA gyrase or topoisomerase IV by binding with enzyme-DNAb inaryc omplexes to form ternary supramolecular complexes, therebyo bstructing DNA replication and finally resulting in bacterial death. [6][7][8] However, the overuse of quinolones to manage bacterial infections has led to the evolution and widespread distribution of resistant strains,s uch as Streptococcus pneumoniae, Escherichia coli,a nd Staphylococcus aureus.…”
Section: Introductionmentioning
confidence: 99%
“…This compound compares favorably with the most advanced inhibitors from two recently described medicinal chemistry efforts targeting Ndh-2: quinolinyl pyrimidines and a quinolone series. [8] The MIC 50 values of the most potent compounds from either of these two series ranged from 0.14–1.0 μM. Likewise, no compounds from a suite of phenothiazine-derived compounds gave MIC 50 values below 10 μM against aerobic Mtb.…”
mentioning
confidence: 99%